How Does Childbirth Alter Intrahousehold Resource Allocation?: Evidence from Japan - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2013)
Exploiting unique panel data that include direct measurements of resource allocation within households, we investigated the impact of childbirth on intrahousehold allocation for married Japanese couples. Based on a collective model of the household, we developed reduced-form and structural-form estimation equations that allow us to focus on private goods to track the changes in intrahousehold resource allocation. We found one additional child is associated with a reduction in the wife's private expenditure share by at least two percentage points. This may be because she substitutes more say in decisions on the children for her own private expenditure share.